Volume 1A: Combustion, Fuels and Emissions 2013
DOI: 10.1115/gt2013-94796
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Lean Burn Module Air Blast Pilot Injector With Laser Techniques

Abstract: For lean burn combustor development in low emission aero-engines, the pilot stage of the fuel injector plays a key role with respect to stability, operability, NOx emissions, and smoke production. Therefore it is of considerable interest to characterize the pilot module in terms of pilot zone mixing, fuel placement, flow field and interaction with the main stage. This contribution focusses on the investigation of soot formation during pilot-only operation. Optical test methods were applied in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Only pilot burner is fueled at the low power settings, such as idle and approach conditions, and the pilot and main burner are both fueled at high power settings, such as climb and take-off conditions. Compared with fuel injection devices in previous work, [6][7][8][9] the pilot swirl cup injector optimizes both the pressure swirl atomizer and swirler to improve the spray quality in terms of fuel/air mixing and spatial distribution by adjusting characteristics of primary spray, structure of venturi prefilmer, and air mass flow ratio of two swirlers, etc. such as, enlargement of spray cone for enhancing interactions between primary spray and swirling air, and augment of the operating range of pressure swirl atomizer in pilot stage for ensuring spray quality both at the low and high power settings.…”
Section: Lean-staged Multi-injection Fuel Injectormentioning
confidence: 99%
See 1 more Smart Citation
“…Only pilot burner is fueled at the low power settings, such as idle and approach conditions, and the pilot and main burner are both fueled at high power settings, such as climb and take-off conditions. Compared with fuel injection devices in previous work, [6][7][8][9] the pilot swirl cup injector optimizes both the pressure swirl atomizer and swirler to improve the spray quality in terms of fuel/air mixing and spatial distribution by adjusting characteristics of primary spray, structure of venturi prefilmer, and air mass flow ratio of two swirlers, etc. such as, enlargement of spray cone for enhancing interactions between primary spray and swirling air, and augment of the operating range of pressure swirl atomizer in pilot stage for ensuring spray quality both at the low and high power settings.…”
Section: Lean-staged Multi-injection Fuel Injectormentioning
confidence: 99%
“…Such pilot flames produce high smoke, CO, and UHC emissions and have poor stability. Recently, Meier et al 8 studied the effect of air/fuel ratio on soot formation during pilot-only operation by planar laser-induced incandescence (LII), it was found that soot is formed predominantly in the upstream directed part of the shaped pilot flow near the interface to the outer main flow. Kobayashi et al 9 investigated effects of swirler angle and swirler lip configurations on ignition performance, ignition performance was improved by extending heat shield to suppress the interaction of pilot flame and the main air stream, but other important performances of combustion were ignored.…”
Section: Introductionmentioning
confidence: 99%